Olympic weightlifting and plyometric training with children provides similar or greater performance improvements than traditional resistance training - Chaouachi, A.; Hammami, R.; Kaabi, S.; Chamari, K.; Drinkwater, E. J.; Behm, D. G. (The Journal of Strength and Conditioning Research, 2014)
A number of organizations recommend that advanced resistance training (RT) techniques can be implemented with children. The objective of this study was to evaluate the effectiveness of Olympic-style weightlifting (OWL), plyometrics, and traditional RT programs with children. Sixty-three children (10-12 years) were randomly allocated to a 12-week control OWL, plyometric, or traditional RT program. Pre- and post-training tests included body mass index (BMI), sum of skinfolds, countermovement jump (CMJ), horizontal jump, balance, 5- and 20-m sprint times, isokinetic force and power at 60 and 300°/s. Magnitude-based inferences were used to analyze the likelihood of an effect having a standardized (Cohen's) effect size exceeding 0.20. All interventions were generally superior to the control group. Olympic weightlifting was >80% likely to provide substantially better improvements than plyometric training for CMJ, horizontal jump, and 5- and 20-m sprint times, whereas >75% likely to substantially exceed traditional RT for balance and isokinetic power at 300°/s. Plyometric training was >78% likely to elicit substantially better training adaptations than traditional RT for balance, isokinetic force at 60 and 300°/s, isokinetic power at 300°/s, and 5- and 20-m sprints. Traditional RT only exceeded plyometric training for BMI and isokinetic power at 60°/s. Hence, OWL and plyometrics can provide similar or greater performance adaptations for children. It is recommended that any of the 3 training modalities can be implemented under professional supervision with proper training progressions to enhance training adaptations in children.